Pengaruh Kemandirian dan Gaya Belajar Terhadap Hasil Belajar Dengan Variabel Mediasi Motivasi Belajar - Nadia Virany Khusnul Khotimah; Eko Wahjudi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
This study aims to determine the role of the learning motivation variable as a mediation between the influence of independent learning and the influence of learning styles on learning outcomes in Universitas Negeri Surabaya Accounting Education students. This type of research used in this research is a type of quantitative research. The data collection techniques used in this study were questionnaires and documentation. Data processing in this study using SEM analysis techniques. The conclusions obtained based on this research are learning independence can affect learning motivation directly, learning style can affect learning motivation directly, learning outcomes are directly influenced by learning motivation, learning motivation cannot be a variable that mediates learning independence on learning outcomes, learning motivation cannot mediate learning styles on learning outcomes.